Diagnoses, Decisions, and Outcomes: Web Search as Decision Support for Cancer - Paul, Michael J.; White, Ryen W.; Horvitz, Eric (2015)
People diagnosed with a serious illness often turn to the Web for their rising information needs, especially when decisions are required. We analyze the search and browsing behavior of searchers who show a surge of interest in prostate cancer. Prostate cancer is the most common serious cancer in men and is a leading cause of cancer-related death. Diagnoses of prostate cancer typically involve reﬂection and decision making about treatment based on assessments of preferences and outcomes. We annotated timelines of treatment-related queries from nearly 300 searchers with tags indicating diﬀerent phases of treatment, including decision making, preparation, and recovery. Using this corpus, we present a variety of analyses toward the goal of understanding search and decision making about treatments. We characterize search queries and the content of accessed pages for diﬀerent treatment phases, model search behavior during the decision making phase, and create an aggregate alignment of treatment timelines illustrated with a variety of visualizations. The experiments provide insights about how people who are engaged in intensive searches about prostate cancer over an extended period of time pursue and access information from the Web.